High-stability electrode for extracting lithium from lithium-containing solution and preparation method of high-stability electrode
The electrochemical deintercalation method is solved by preparing carbon-covered electrode materials in alkaline lithium-containing solutions by using polyanionic materials and organic carbon sources, and combining conductive agents, binders, pore-forming agents and hydrophilic modifiers. The problem of poor circulation stability achieves efficient and deep lithium extraction effect.
Patent Information
- Application Number
- CN202411573791.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
AI Technical Summary
The existing electrochemical deintercalation method has problems such as poor circulation stability, low adsorption capacity, low current density, low current efficiency and low lithium recovery in alkaline lithium-containing solutions.
采用聚阴离子材料作为活性材料,通过与有机碳源混合高温焙烧形成碳包覆结构,并与导电剂、粘结剂、造孔剂和亲水改性剂混合制备电极,提高电极的导电性和 Hydrophilicity.
The electrode is able to achieve high cycle stability, high current density, high lithium recovery rate and high current efficiency in alkaline lithium-containing solutions, and can deeply extract lithium.
Smart Images

Figure CN119391982A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium resource development and utilization, and in particular to a high-stability electrode for extracting lithium from a lithium-containing solution and a preparation method thereof. Background Art
[0002] As a strategic key metal, lithium has a wide range of applications in metallurgy, chemical industry, medicine, and new energy. With the gradual popularization of new energy vehicles, the demand for lithium salts as the main raw material for power batteries has grown rapidly, and the contradiction between supply and demand has become increasingly severe. How to efficiently develop lithium resources is of great significance to promoting the sustainable development of the new energy industry. Lithium resources are mainly found in lithium-containing minerals such as spodumene, lepidolite, phosphate lithium aluminum, and petalite, as well as salt lake brine, underground brine, and oilfield brine. The amount of lithium resources in salt lake brine accounts for more than 70% of the world's total lithium resources. In my country, salt lake lithium resources are mainly distributed in the Qinghai-Tibet Plateau, such as the Dongtaijinaier Salt Lake, the Xitaijinaier Salt Lake, and the Chaerhan Salt Lake in Qinghai, and the Zabuye Salt Lake and Jiezechaka Salt Lake in Tibet, all of which are large lithium-containing salt lakes.
[0003] At present, the main methods for extracting lithium from salt lake brine include precipitation, adsorption, calcination, extraction, electrodialysis, electrochemical deintercalation, etc. The precipitation method is mainly used in the high-quality salt lakes in the "Lithium Triangle" of South America with a low magnesium-to-lithium ratio. The adsorption method, calcination method, extraction method and electrodialysis method are mainly lithium extraction technologies developed for salt lake brines with a high magnesium-to-lithium ratio. The electrochemical deintercalation method uses the high selectivity of electrode materials for lithium, that is, the electrode materials can selectively embed lithium from brine with complex components to achieve lithium and other impurity ions (Na + , K + , Ca 2+ Mg 2+ ) has the advantages of strong adaptability to brine, high selectivity of electrode materials for lithium, and low energy consumption; it can obtain lithium-rich liquid with higher lithium concentration and the lithium extraction process is green and environmentally friendly.
[0004] For the electrochemical deintercalation process of lithium extraction, the cyclic stability of its electrode materials is related to the frequency of electrode replacement, which in turn affects production efficiency and production costs. At present, the electrode materials used for electrochemical lithium extraction, such as lithium iron phosphate, have good cycle performance in neutral lithium-containing solutions, and can be cyclically extracted for more than thousands of times while still maintaining a high lithium adsorption capacity. However, when used in alkaline lithium-containing solutions, there is a problem of rapid capacity decay. The reason is that when the electrode material electrochemically deintercalates lithium in an alkaline lithium-containing solution, irreversible reactions are prone to occur to generate FeOOH, etc., thereby gradually losing the ability to selectively extract lithium. In addition, electrode active materials are generally coated with carbon to enhance their conductivity, but the electrode active materials after carbon coating are often relatively hydrophobic and have poor wettability, resulting in the inability to extract lithium at high current densities.
[0005] In summary, in order to achieve the efficient development and utilization of lithium resources in lithium-containing solutions, especially alkaline lithium-containing solutions (alkaline salt lake brine, lithium carbonate lithium precipitation mother liquor), it is urgent to develop new lithium extraction materials with stable lithium deintercalation and good hydrophilicity. Summary of the invention
[0006] In view of the above analysis, the present invention aims to provide a high-stability electrode for extracting lithium from a lithium-containing solution and a preparation method thereof, so as to solve at least one of the problems in the prior art, such as poor electrode cycle stability, low adsorption capacity, low current density, low current efficiency, and low lithium recovery rate.
[0007] In a first aspect, the present invention provides a method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution, comprising the following steps:
[0008] (1) Using a polyanion material as an active material, mixing the active material with an organic carbon source, and calcining at high temperature to obtain a carbon-coated active material;
[0009] (2) The carbon-coated active material is mixed with a conductive agent, a binder, a pore-forming agent and a hydrophilic modifier, and then a solvent is added to obtain a slurry. The slurry is coated on a current collector and dried to obtain the electrode.
[0010] Furthermore, in step (1), the polyanion material includes a silicate polyanion material and / or a titanate polyanion material.
[0011] Furthermore, the silicate type polyanion material includes one or more of lithium iron silicate, lithium manganese silicate, lithium manganese iron silicate and their derivatives;
[0012] The titanate type polyanion material includes one or more of lithium iron titanate, lithium manganese titanate, lithium manganese iron titanate and their derivatives.
[0013] Furthermore, in step (1), the organic carbon source includes at least one of glucose, sucrose, and citric acid.
[0014] Furthermore, in step (1), the high temperature calcination temperature is 400-700° C., and the calcination time is 3-10 hours.
[0015] Furthermore, in step (2), the mass ratio of the carbon-coated active material, the conductive agent, the binder, the pore-forming agent and the hydrophilic modifier is 7-9:1-2:1-2:3-5:0.5-1, and the mass of the solvent is 1-3 times the mass of the carbon-coated active material.
[0016] Furthermore, in step (2), the conductive agent includes at least one of acetylene black, superP, Ketjen black, and carbon nanotubes;
[0017] and / or, the binder comprises polyvinylidene fluoride (PVDF);
[0018] And / or, the pore-forming agent includes at least one of sodium chloride, sodium sulfate, potassium chloride and potassium sulfate;
[0019] and / or, the hydrophilic modifier is at least one of polyvinyl pyrrolidone (PVP), polyethylene glycol or polyvinyl alcohol;
[0020] And / or, the solvent comprises N-methylpyrrolidone (NMP).
[0021] Furthermore, in step (2), the current collector includes at least one of a titanium-based current collector and a carbon-based current collector.
[0022] Furthermore, in step (2), the coating density of the slurry is 50 to 120 mg / cm 2 The drying temperature is 50-90℃ and the drying time is 8-20h.
[0023] In a second aspect, the present invention provides an electrode prepared by the above method.
[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0025] (1) The polyanion material in the electrode of the present invention selects polyanion groups containing strong bond energy chemical bonds, such as silicon-oxygen tetrahedrons formed by Si-O bonds and titanium-oxygen octahedrons formed by Ti-O bonds. The crystal structure constructed by the polyanion group has stronger stability than the phosphorus-oxygen tetrahedron formed by PO bonds, and can effectively fix transition metal ions in the crystal structure of the material, preventing transition metal elements such as Fe and Mn in the active material from being difficult to dissolve or migrate in lithium-containing solutions, thereby improving the cycle stability of the electrode at the source; in the present invention, an organic carbon source is used to perform high-temperature carbon coating on the active material to improve the conductivity of the material, reduce the charge transfer impedance in the electrochemical process, and realize stable and efficient extraction of lithium; and the carbon-coated electrode material is hydrophilically modified, and the electrode prepared by the present invention has good hydrophilicity and lubricity;
[0026] (2) The electrode prepared by the method of the present invention has good cycle performance, good lithium extraction performance, large current lithium extraction, high current efficiency, high lithium recovery rate, and can achieve deep lithium extraction from brine;
[0027] (3) The electrode preparation method provided by the present invention has the advantages of low cost and simple process, and is easy to realize industrial application.
[0028] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0030] Figure 1 The cycle performance diagram of the electrode in the electrochemical lithium extraction body constructed in Examples 1-6 of the present invention;
[0031] Figure 2 It is a comparison diagram of the current density of Example 1 and Comparative Examples 1-2 in the present invention;
[0032] Figure 3 It is a cycle performance diagram of the electrodes of Comparative Example 3 and Example 1 in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0034] A specific embodiment of the present invention discloses a method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution, comprising the following steps:
[0035] (1) Using a polyanion material as an active material, mixing the active material with an organic carbon source, and calcining at high temperature to obtain a carbon-coated active material;
[0036] (2) The carbon-coated active material is mixed with a conductive agent, a binder, a pore-forming agent and a hydrophilic modifier, and then a solvent is added to obtain a slurry. The slurry is coated on a current collector and dried to obtain the electrode.
[0037] It should be noted that the lithium-containing solution described in the present invention is a neutral or alkaline lithium-containing solution, preferably, the pH value is 6 to 13. The electrode of the present invention has the advantages of good cycle stability, high current density, high lithium recovery rate, etc. in a neutral or alkaline lithium-containing solution.
[0038] In a specific embodiment, in step (1), the polyanion material includes a silicate polyanion material and / or a titanate polyanion material.
[0039] Preferably, the silicate polyanion material includes lithium iron silicate (Li2FeSiO4), lithium manganese silicate (Li2MnSiO4), lithium manganese iron silicate (Li2Fe x Mn 1-x SiO4, 0<x<1) and one or more of its derivatives;
[0040] The titanate-type polyanion materials include lithium iron titanate (Li2FeTiO4), lithium manganese titanate (Li2MnTiO4), lithium manganese titanate (Li2Fe x Mn 1-x TiO4, 0<x<1) and one or more of its derivatives.
[0041] The polyanion materials of the present invention are all commercially available raw materials or are prepared by existing methods.
[0042] It should be noted that the polyanion material of the present invention contains polyanion groups with strong bond energy chemical bonds, such as silicon-oxygen tetrahedrons composed of Si-O bonds and titanium-oxygen octahedrons composed of Ti-O bonds. The crystal structure constructed by the polyanion group has stronger stability than the phosphorus-oxygen tetrahedron composed of PO bonds, and can effectively fix transition metal ions in the crystal structure of the material, preventing transition metal elements such as Fe and Mn in the active material from being difficult to dissolve or migrate in lithium-containing solutions, thereby improving the cycle stability of the electrode at the source; the inventors have estimated thermodynamic parameters and performed thermodynamic calculations on the silicate-type polyanion material lithium iron silicate, and found that the pH values of lithium iron silicate and lithium iron titanate that undergo irreversible reactions in aqueous solutions are both above 12, while the pH value of lithium iron phosphate that undergoes irreversible reactions in aqueous solutions is only about 9.5, which indicates that the stability of silicate-type polyanion materials in alkaline or even strongly alkaline solutions will be significantly better than that of lithium iron phosphate.
[0043] In a specific embodiment, in step (1), the organic carbon source includes at least one of glucose, sucrose, and citric acid.
[0044] Preferably, the mass of the organic carbon source is 0.1 to 0.8 times the mass of the active material, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 times. The present invention selects the above range because too low a ratio leads to poor conductivity, while too high a ratio leads to strong hydrophobicity and decreased adsorption capacity.
[0045] In a specific embodiment, in step (1), the temperature of high temperature roasting is 400-700°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, and the roasting time is 3-10h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. The present invention selects the above temperature and roasting time to ensure that the desired product is obtained, and the high temperature or long time leads to an increase in the particle size, which reduces the diffusion coefficient of the ions and reduces the efficiency of lithium extraction.
[0046] It should be noted that in the present invention, an organic carbon source is used to perform high-temperature carbon coating on the active material to improve the conductivity of the material, reduce the charge transfer impedance in the electrochemical process, and achieve high current density and efficient extraction of lithium; in addition, carbon coating can buffer the volume expansion of the active material during the charge and discharge process, improve the electrochemical stability of the material, and achieve stable extraction of lithium.
[0047] In a specific embodiment, in step (2), the mass ratio of the carbon-coated active material, the conductive agent, the binder, the pore-forming agent and the hydrophilic modifier is 7-9:1-2:1-2:3-5:0.5-1, and the mass of the solvent is 1-3 times the mass of the carbon-coated active material, for example, 1 times, 1.2 times, 1.4 times, 1.6 times, 1.8 times, 2 times, 2.2 times, 2.4 times, 2.6 times, 2.8 times, 3 times. Within this range, the slurry has a certain viscosity and is suitable for coating; below the above range, the slurry is too thin and the electrode is prone to cracking, and too high a viscosity is not conducive to coating.
[0048] The carbon-coated active material is coated with a very hydrophobic carbon layer on its surface, which easily leads to poor wettability of the active material in aqueous solution, thereby hindering the transfer of lithium ions in the solution to the electrode surface. Therefore, the carbon-coated electrode material needs to be hydrophilic modified; since the molecular structure of polyvinyl pyrrolidone (PVP) contains a lactam group with a large polarity, its coating quickly absorbs water when it comes into contact with water, and the water molecules form a hydrogel through hydrogen bonding, thus showing good hydrophilicity and lubricity; in addition, PVP is soluble in NMP solvent, so the modification of lithium-extracting active materials can be achieved simultaneously during the slurry preparation process.
[0049] During the electrode preparation process, it is necessary to control the ratio of active materials, conductive agents, binders, pore-forming agents, and hydrophilic modifiers to obtain electrodes with good conductivity, strong hydrophilicity, and excellent mass transfer effects.
[0050] In the present invention, in order to solve the problem that the carbon-coated active material has poor wettability after carbon coating, a three-dimensional porous network hydrophilic electrode is constructed by adding a pore-forming agent and a hydrophilic modifier during the electrode preparation process, thereby shortening the transmission distance of lithium ions in the solution inside the electrode material, enhancing the transmission effect of lithium ions in the solution, achieving high current density lithium extraction, and increasing the rate of the lithium extraction process.
[0051] In a specific embodiment, in step (2), the conductive agent includes at least one of acetylene black, superP, Ketjen black, and carbon nanotubes;
[0052] and / or, the binder comprises polyvinylidene fluoride (PVDF);
[0053] And / or, the pore-forming agent includes at least one of sodium chloride, sodium sulfate, potassium chloride and potassium sulfate;
[0054] and / or, the hydrophilic modifier is at least one of polyvinyl pyrrolidone (PVP), polyethylene glycol or polyvinyl alcohol;
[0055] The inventors have found through a large number of experiments that when the hydrophilic modifier is polyvinyl pyrrolidone, the prepared electrode has a high current density and Li + The adsorption capacity, current efficiency and lithium recovery rate are better.
[0056] And / or, the solvent comprises N-methylpyrrolidone (NMP).
[0057] The hydrophilic modifier of the present invention enhances the wetting performance of the carbon-coated active material, strengthens the mass transfer process of lithium ions in the solution to the surface and interior of the electrode, and realizes lithium extraction at a high current density.
[0058] In a specific embodiment, in step (2), the current collector includes at least one of a titanium-based current collector and a carbon-based current collector.
[0059] In a specific embodiment, in step (2), the coating density of the slurry is 50-120 mg / cm 2 , for example, 50 mg / cm 2 、60mg / cm 2 、70mg / cm 2 、80mg / cm 2 、90mg / cm 2 、100mg / cm 2 、110mg / cm 2 、120mg / cm 2The drying temperature is 50-90°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, and the drying time is 8-20h, for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h.
[0060] It should be noted that if the coating density is too low, the overall adsorption capacity of the electrode will be low; if the coating density is too high, it will be unfavorable for the mass transfer of ions in the solution inside the electrode; if the drying temperature is low, the drying time will be long; if the drying temperature is too high, the electrode will easily crack.
[0061] After obtaining the lithium extraction slurry, it needs to be evenly coated on the current collector; because the current collector used must be stable in aqueous solution and can be used as both an anode current collector and a cathode current collector.
[0062] The preparation method of the electrode of the present invention has the advantages of low cost, simple process and the like, and is easy to realize industrial application.
[0063] Another specific embodiment of the present invention discloses an electrode prepared by the above method.
[0064] The average current density of the electrode of the present invention during the lithium extraction process is greater than 22.89A / m 2 , electrode material Li + The adsorption capacity is greater than 28.39 mg / g, the current efficiency is greater than 89.65%, the lithium recovery rate is greater than 88.85%, and after 50 cycles, the capacity retention rate is ≥96.62%.
[0065] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0066] Example 1
[0067] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0068] (1) Li2FeSiO4 was used as the lithium-extracting active material, and it was evenly mixed with glucose, an organic carbon source, wherein the mass of glucose was 0.6 times the mass of Li2FeSiO4, and then the mixture was calcined at 400°C for 10 h to obtain the carbon-coated active material Li2FeSiO4@C;
[0069] (2) The above-mentioned Li2FeSiO4@C was mixed with the conductive agent acetylene black, the binder PVDF, the pore-forming agent sodium chloride, the hydrophilic modifier PVP, etc. in a mass ratio of 7:1:1:3:0.5, and then 1 times the mass of the carbon-coated active material was added to the N-methylpyrrolidone (NMP) solvent for slurrying. Then, the lithium extraction slurry was coated with a density of 120 mg / cm 2 It is uniformly coated on a titanium-based current collector and dried at 90° C. for 8 h to obtain a Li2FeSiO4@C electrode (the high-stability electrode for extracting lithium from a lithium-containing solution).
[0070] A lithium-poor state Li 2-x Preparation of FeSiO4@C (0<x<2, the same below) electrode: Li2FeSiO4@C electrode was used as anode and nickel foam was used as cathode. Lithium-poor Li was prepared by electrolysis in sodium chloride solution for 12 h. 2-x FeSiO4@C electrode;
[0071] Li2FeSiO4@C electrode was used as anode and lithium-poor Li 2-x FeSiO4@C was used as cathode, brine as cathode liquid and sodium chloride solution as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from alkaline salt lake brine. The main components (g / L) and pH of brine are shown in Table 1. The results show that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0072] Table 1
[0073] Element Li Na K Cl S <![CDATA[HCO3 - ]]> <![CDATA[CO3 2- ]]> <![CDATA[B2O3]]> pH Concentration (g / L) 0.38 55.13 8.68 68.12 5.84 0.45 12.36 2.55 9.63
[0074] Example 1-1
[0075] The preparation method of the electrode and the construction of the electrochemical lithium extraction system in this embodiment are the same as those in Example 1, except that the hydrophilic modifier is polyethylene glycol. + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0076] Example 1-2
[0077] The preparation method of the electrode and the construction of the electrochemical lithium extraction system in this embodiment are the same as those in Example 1, except that the hydrophilic modifier is polydiluted ethanol. + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0078] Example 2
[0079] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0080] (1) Li2MnSiO4 was used as the lithium extraction active material, and it was evenly mixed with sucrose, an organic carbon source, with the mass of sucrose being 0.1 times the mass of Li2MnSiO4. The mixture was then calcined at 600°C for 5h to obtain the carbon-coated active material Li2MnSiO4@C.
[0081] (2) The above-mentioned Li2MnSiO4@C was mixed with conductive agent super P, binder PVDF, pore-forming agent potassium chloride, hydrophilic modifier PVP, etc. in a mass ratio of 9:1:1:5:1, and then N-methylpyrrolidone (NMP) solvent with a mass of 2 times that of the carbon-coated active material was added to make a slurry. Then, the lithium extraction slurry was coated at a density of 50 mg / cm 2 It was uniformly coated on a carbon-based current collector and dried at 50°C for 20 h to obtain a Li2MnSiO4@C electrode.
[0082] A lithium-poor state Li 2-x Preparation of MnSiO4@C (0<x<2, the same below) electrode: Li2MnSiO4@C electrode was used as anode and graphite plate as cathode, and lithium was electrolyzed in sodium bicarbonate solution for 12h to prepare lithium-poor Li 2-x MnSiO4@C electrode;
[0083] Li2MnSiO4@C electrode was used as anode and Li-deficient Li 2-x MnSiO4@C was used as cathode, brine was used as cathode liquid, and sodium chloride solution was used as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from salt lake brine. The brine composition was the same as that in Example 1. The results showed that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0084] Example 3
[0085] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0086] (1) Li2Fe x Mn 1-x SiO4 (0<x<1, the same below) is used as the active material for lithium extraction, and it is mixed evenly with citric acid, an organic carbon source. The mass of citric acid is Li2Fe x Mn 1-x The mixture was then calcined at 700 °C for 3 h to obtain the carbon-coated active material Li2Fe x Mn1-x SiO4@C;
[0087] (2) The above Li2Fe x Mn 1-x SiO4@C was mixed with the conductive agent Ketjen black, the binder PVDF, the pore-forming agent sodium sulfate, the hydrophilic modifier PVP, etc. at a mass ratio of 7:2:1:4:0.8, and then three times the mass of the carbon-coated active material was added to make a slurry with N-methylpyrrolidone (NMP) solvent. Then, the lithium extraction slurry was coated with a density of 80 mg / cm 2 It was evenly coated on the carbon-based current collector and dried at 70 °C for 14 h to obtain Li2Fe x Mn 1-x SiO4@C electrode.
[0088] A lithium-poor state Li 2-y Fe x Mn 1-x Preparation of SiO4@C (0<y<2, the same below) electrode: Li2Fe x Mn 1-x SiO4@C electrode was used as anode and graphite plate as cathode, and lithium-poor Li was prepared by electrolysis in sodium chloride solution for 12 h. 2-y Fe x Mn 1-x SiO4@C electrode;
[0089] Li2Fe x Mn 1-x SiO4@C electrode as anode, lithium-poor Li 2-y Fe x Mn 1-x SiO4@C was used as cathode, brine was used as cathode liquid, and sodium chloride solution was used as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from salt lake brine. The brine composition was the same as that in Example 1. The results showed that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0090] Example 4
[0091] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0092] 1) Li2FeTiO4 was used as the lithium extraction active material, and it was evenly mixed with glucose, an organic carbon source, wherein the mass of glucose was 0.5 times the mass of Li2FeTiO4, and then the mixture was calcined at 500°C for 8h to obtain the carbon-coated active material Li2FeTiO4@C;
[0093] (2) The above-mentioned Li2FeTiO4@C was mixed with the conductive agent acetylene black and carbon nanotubes, the binder PVDF, the pore-forming agent potassium sulfate, the hydrophilic modifier PVP, etc. in a mass ratio of 7:1:2:3:0.7, and then 2.5 times the mass of the carbon-coated active material was added to the N-methylpyrrolidone (NMP) solvent for slurrying. Then, the lithium extraction slurry was coated with a density of 100 mg / cm 2 It was uniformly coated on a carbon-based current collector and dried at 80 °C for 14 h to obtain a Li2FeTiO4@C electrode.
[0094] A lithium-poor state Li 2-x Preparation of FeTiO4@C (0<x<2, the same below) electrode: Li2FeTiO4@C electrode was used as anode and nickel foam was used as cathode. Lithium-poor Li was prepared by electrolysis in sodium chloride solution for 12 h. 2-x FeTiO4@C electrode;
[0095] Li2FeTiO4@C electrode was used as anode and lithium-poor Li 2-x FeTiO4@C was used as cathode, brine was used as cathode liquid, and sodium chloride solution was used as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from salt lake brine. The brine composition was the same as that in Example 1. The results showed that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0096] Example 5
[0097] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0098] (1) Li2MnTiO4 was used as the lithium extraction active material, and it was evenly mixed with glucose, an organic carbon source, wherein the mass of glucose was 0.8 times the mass of Li2MnTiO4, and then the above mixture was calcined at 600°C for 6h to obtain the carbon-coated active material Li2MnTiO4@C;
[0099] (2) The above-mentioned Li2MnTiO4@C was mixed evenly with the conductive agent carbon nanotubes, the binder PVDF, the pore-forming agent sodium chloride, the hydrophilic modifier PVP, etc. in a mass ratio of 7:2:2:4:0.9, and then N-methylpyrrolidone (NMP) solvent with a mass of 3 times that of the carbon-coated active material was added to make a slurry. Then, the lithium extraction slurry was coated with a coating density of 110 mg / cm 2 It was uniformly coated on a carbon-based current collector and dried at 90°C for 10 h to obtain a Li2MnTiO4@C electrode.
[0100] A lithium-poor state Li 2-xPreparation of MnTiO4@C (0<x<2, the same below) electrode: Li2MnTiO4@C electrode was used as anode and nickel foam was used as cathode. Lithium-poor Li was prepared by electrolysis in sodium chloride solution for 12 h. 2-x MnTiO4@C electrode;
[0101] Li2MnTiO4@C electrode was used as anode and lithium-poor Li 2-x MnTiO4@C was used as cathode, brine was used as cathode liquid, and sodium chloride solution was used as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from salt lake brine. The brine composition was the same as that in Example 1. The results showed that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0102] Example 6
[0103] A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution in this embodiment specifically comprises the following steps:
[0104] (1) Li2Fe x Mn 1-x TiO4 (0<x<1, the same below) is used as the active material for lithium extraction, and it is mixed evenly with the organic carbon source sucrose. The mass of sucrose is Li2Fe x Mn 1-x The mixture was then calcined at 550 °C for 6 h to obtain the carbon-coated active material Li2Fe x Mn 1-x TiO4@C;
[0105] Among them, Li2Fe x Mn 1-x The preparation method of TiO4 is as follows: Li2CO3 (5% Li-excess), Fe(NO3)2·9H2O, Mn(NO3)2·4H2O and Ti[OCH(CH3)2]4 are added to an isopropanol solution in a stoichiometric ratio under vigorous stirring. After evaporation of the solvent, the dry gel is vacuum dried at 90°C for 8 hours and then sintered at 600°C for 4 hours under flowing argon to obtain lithium manganese iron titanate (Li2Fe x Mn 1-x TiO4).
[0106] (2) The above Li2Fe x Mn 1-xTiO4@C was mixed with the conductive agent Ketjen black, the binder PVDF, the pore-forming agent sodium sulfate, the hydrophilic modifier PVP, etc. at a mass ratio of 8:1:1:5:0.9, and then N-methylpyrrolidone (NMP) solvent (2 times the mass of the carbon-coated active material) was added to make a slurry. Then, the lithium extraction slurry was coated at a density of 95 mg / cm 2 It was evenly coated on the carbon-based current collector and dried at 85 °C for 12 h to obtain Li2Fe x Mn 1-x TiO4@C electrode.
[0107] A lithium-poor state Li 2-y Fe x Mn 1-x Preparation of TiO4@C (0<y<2, the same below) electrode: Li2Fe x Mn 1-x TiO4@C electrode was used as anode and graphite plate as cathode, and lithium-poor Li was prepared by electrolysis in sodium chloride solution for 12 h. 2-y Fe x Mn 1-x TiO4@C electrode;
[0108] Li2Fe x Mn 1-x TiO4@C electrode as anode, lithium-poor Li 2-y Fe x Mn 1-x TiO4@C was used as cathode, brine was used as cathode liquid, and sodium chloride solution was used as anode liquid to construct an electrochemical lithium extraction system to selectively extract lithium from salt lake brine. The brine composition was the same as that in Example 1. The results showed that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0109] Example 7
[0110] The present embodiment provides a method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution. The method is the same as that in Example 1. The lithium-containing solution treated is sulfate-type salt lake brine. The composition of the brine is shown in Table 2. The method described in Example 1 is used to selectively extract lithium from the brine. The results show that the average current density, electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0111] Based on the results of Example 1 and Example 7, it can be found that the lithium extraction active material and the electrode thereof provided by the present invention have good lithium extraction performance in different types of brine, that is, the brine adaptability is strong.
[0112] Table 2 Composition and pH of sulfate brine
[0113] <![CDATA[ 成 Minutes]]> <![CDATA[ L i]]> <![CDATA[ N a]]> <![CDATA[ K ]]> <![CDATA[ C a]]> <![CDATA[ M g]]> <![CDATA[ C l]]> <![CDATA[ SO 4 2- ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[ <h2 style=";text-align:left;direction:ltr"> B2 <h2 style=";text-align:left;direction:ltr"> o3]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[p H ]]> Concentration (g / L) 0.42 22.72 2.86 0.31 2.83 34.65 16.75 1.57 7.32
[0114] Comparative Example 1
[0115] The preparation method of the electrode of this comparative example is the same as that of Example 1, except that in step (1), glucose is not used to coat Li2FeSiO4.
[0116] The electrode prepared in this comparative example was made into a lithium-deficient lithium iron silicate electrode by the method of Example 1, and an electrochemical lithium extraction system was constructed by the method of Example 1. The lithium extraction steps were the same as those in Example 1.
[0117] The results show that the average current density and electrode material Li during lithium extraction of lithium iron silicate are not treated with carbon coating. + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0118] Comparative Example 2
[0119] The preparation method of the electrode of this comparative example is the same as that of Example 1, except that in step (2), the hydrophilic modifier PVP is not added, but Li2FeSiO4@C is mixed with the conductive agent acetylene black, the binder PVDF, and the pore-forming agent sodium chloride in a mass ratio of 7:1:1:3 to prepare a slurry. The electrode prepared in this comparative example is made into a lithium-deficient lithium iron silicate electrode by the method of Example 1, and the electrochemical lithium extraction system is constructed by the method of Example 1, and the lithium extraction step is the same as that of Example 1.
[0120] The results show that the average current density and electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0121] Comparative Example 3
[0122] The preparation method of the electrode of this comparative example is the same as that of Example 1, except that in step (1), lithium iron phosphate is used as the active material.
[0123] The electrode prepared in this comparative example was made into a lithium-deficient lithium iron phosphate electrode by the method of Example 1, and an electrochemical lithium extraction system was constructed by the method of Example 1. The lithium extraction steps were the same as those in Example 1.
[0124] The results show that the average current density and electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0125] Comparative Example 4
[0126] The preparation method of the electrode and the construction of the electrochemical lithium extraction system of this comparative example are the same as those of Example 1, except that in step (1), the high-temperature calcination temperature is 350° C. and the calcination time is 11 h.
[0127] The results show that the average current density and electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0128] Comparative Example 5
[0129] The preparation method of the electrode and the construction of the electrochemical lithium extraction system of this comparative example are the same as those of Example 1, except that in step (1), the mass of glucose is 0.85 times the mass of Li2FeSiO4.
[0130] The results show that the average current density and electrode material Li + The adsorption capacity, current efficiency and lithium recovery rate are shown in Table 3.
[0131] Table 3
[0132]
[0133]
[0134] According to Table 3, compared with Example 1, Example 1-1 and Example 1-2, when the hydrophilic modifier is polyvinyl pyrrolidone, the current density and Li + The adsorption capacity, current efficiency and lithium recovery rate are higher than those of polyethylene glycol and polyvinyl alcohol.
[0135] Compared with Example 1, in Comparative Example 1, the lithium iron silicate is not subjected to carbon coating treatment, and the current density and adsorption capacity during lithium extraction are significantly lower than those of the electrode prepared from the carbon-coated lithium iron silicate material provided in Example 1.
[0136] Comparative Example 2 Compared with Example 1, in Comparative Example 1, no hydrophilic modifier is added, and the current density and adsorption capacity are significantly lower than the hydrophilic modified electrode provided in Example 1. Comprehensively comparing the current densities of Example 1, Comparative Example 1 and Comparative Example 2, the results are as follows Figure 2 As shown. By comparison, it can be found that the electrode provided by the present invention has the highest current density and can achieve high current density lithium extraction. At the same time, it also shows that in order to achieve high current density lithium extraction, it is necessary to improve the conductivity of the electrode active material and the hydrophilicity of the electrode. The realization of high current density lithium extraction of the present invention is the result of the comprehensive improvement of electrode conductivity and hydrophilicity.
[0137] Comparative Example 3 Compared with Example 1, in Comparative Example 1, lithium iron phosphate is used as the active material, and the current density and adsorption capacity are slightly lower than those of the lithium iron silicate electrode provided in Example 1. This shows that traditional lithium iron phosphate is not suitable for alkaline lithium-containing solutions (lithium iron phosphate is mainly due to poor cycle performance, not due to problems with current density and adsorption capacity).
[0138] Compared with Example 1, the calcination temperature of Comparative Example 4 is low, the performance of the synthesized electrode active material is poor, and the adsorption capacity and current density are both low, which shows that in order to synthesize high-performance electrode materials, it is necessary to control the appropriate calcination temperature and calcination time.
[0139] In Comparative Example 5, compared with Example 1, the amount of carbon source is increased, which reduces the proportion of active materials and increases the hydrophobicity of the material, which is not conducive to the diffusion of ions in the solution into the interior of the electrode, resulting in a decrease in the adsorption capacity of the electrode material. When using electrodes with the same coating density, the recovery rate of lithium is reduced due to the decrease in adsorption capacity, and deep lithium extraction cannot be achieved.
[0140] Test Example 1
[0141] The electrochemical lithium extraction systems constructed in Examples 1-6 were used to test the cycling performance of the electrode materials in brine with the composition shown in Table 1. Figure 1 As shown in the figure, it can be seen that the electrodes provided in Examples 1-6 have good cycle stability in brine, and after 50 cycles, the capacity retention rate is above 95%.
[0142] Test Example 2
[0143] The electrochemical deintercalation and lithium extraction system was constructed with the lithium iron phosphate electrode provided in this comparative example 3, and the cycle performance of the lithium iron phosphate electrode in brine was tested. The brine composition was the same as that in Example 1. The cycle performance was compared with that of the lithium iron silicate electrode in Example 1. Figure 3 As shown in the figure, after 50 cycles, the capacity retention rate of the lithium iron silicate electrode reaches 96.62%, while the capacity retention rate of the lithium iron phosphate electrode is only 80.95%. This shows that the new lithium extraction material and its electrode provided by the present invention have significantly better cycle stability than the lithium iron phosphate electrode in the electrochemical extraction of lithium from alkaline salt lake brine.
[0144] The inventor has also conducted the above test on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.
[0145] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution, characterized in that: The steps include: (1) Using a polyanion material as an active material, mixing the active material with an organic carbon source, and calcining at high temperature to obtain a carbon-coated active material; (2) The carbon-coated active material is mixed with a conductive agent, a binder, a pore-forming agent and a hydrophilic modifier, and then a solvent is added to obtain a slurry. The slurry is coated on a current collector and dried to obtain the electrode.
2. The method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to claim 1, characterized in that: In step (1), the polyanion material includes a silicate polyanion material and / or a titanate polyanion material.
3. The method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to claim 2, characterized in that: The silicate type polyanion material includes one or more of lithium iron silicate, lithium manganese silicate, lithium manganese iron silicate and their derivatives; The titanate type polyanion material includes one or more of lithium iron titanate, lithium manganese titanate, lithium manganese iron titanate and their derivatives.
4. A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to any one of claims 1 to 3, characterized in that: In step (1), the organic carbon source includes at least one of glucose, sucrose and citric acid.
5. A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to any one of claims 1 to 3, characterized in that: In step (1), the high temperature calcination temperature is 400-700° C., and the calcination time is 3-10 hours.
6. A method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to any one of claims 1 to 3, characterized in that: In step (2), the mass ratio of the carbon-coated active material, the conductive agent, the binder, the pore-forming agent and the hydrophilic modifier is 7-9:1-2:1-2:3-5:0.5-1, and the mass of the solvent is 1-3 times the mass of the carbon-coated active material.
7. The method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to claim 1, characterized in that: In step (2), the conductive agent includes at least one of acetylene black, super P, Ketjen black, and carbon nanotubes; And / or, the binder includes polyvinylidene fluoride; And / or, the pore-forming agent includes at least one of sodium chloride, sodium sulfate, potassium chloride and potassium sulfate; and / or, the hydrophilic modifier is at least one of polyvinyl pyrrolidone, polyethylene glycol or polyvinyl alcohol; And / or, the solvent comprises N-methylpyrrolidone.
8. The method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to claim 1, characterized in that: In step (2), the current collector includes at least one of a titanium-based current collector and a carbon-based current collector.
9. The method for preparing a high-stability electrode for extracting lithium from a lithium-containing solution according to claim 1, characterized in that: In step (2), the coating density of the slurry is 50-120 mg / cm 2 The drying temperature is 50-90℃ and the drying time is 8-20h.
10. An electrode prepared by the method according to any one of claims 1 to 9.